Squalene recovery from palm fatty acid distillate using supercritical fluid extraction - Suleiman, Norhidayah; Baharin, Badlishah Sham; Mirhosseini, Hamed; Sarker, Md. Zaidul Islam (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
The objective of this research is recovery of squalene from palm fatty acid distillate (PFAD) using supercritical fluid extraction (SFE). The extraction process was performed by using the SFE and recovered squalene was analyzed from total lipid extracts using HPLC. A central composite design was used to study the effect of SFE variables namely pressure (X1) from 200 to 400 bar and temperature (X2) from 40 to 60°C on the total lipid extracts (Y1) and squalene concentration (Y2) and optimize the SFE conditions. The nonlinear regression equations were significantly (p < 0.05) fitted for both responses with high R2 (> 0.965), which had no indication of lack of fit. The results indicated that a combined pressure (200 bar) and temperature (50°C) was predicted to provide the optimum region in terms of total lipid extracts (13.84 ± 0.52%) and squalene concentration (418.31 ± 18.40 ppm) studied.